Parental Childcare with Process Benefits. (28th October 2022) - Cosaert, Sam; Hennebel, Veerle
Abstract : Most studies of time allocation in the household draw a sharp line between what is childcare and what is leisure. However, parental time may simultaneously produce welfare for the child and leisure‐like benefits (so‐called process benefits) for the caring parent. We use a flexible model, and its non‐parametric and semi‐parametric implications, to test and quantify these process benefits. Applied to Dutch consumption and time use data, the method predicts that 40% of parental time is also perceived as leisure. Insight into process benefits is crucial for understanding time allocations.